Demonstrating Reading Aloud in Improving EFL Student’s Pronunciation - Latifah, Arifatul; Kristi Nuraini; Henri Fatkurochman; Wahyudi, Diki (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The pronunciation of the English phonemes /ʃ/, /ð/ and /θ/ remains challenging for EFL learners in Indonesia due to the absence of these sounds in the Indonesian Phonological system. A preliminary study conducted with eleventh-grade students at SMK Al-Mu’ien revealed that the average pronunciation score was only 46.97, which was far below the minimum criterian of succes (70). This classroom action research aimed to determine how to improve students’ pronunciation by applying the Reading Aloud technique to XI grade students at SMK Al-Mu’ien in Jember. Data were collected through a pronunciation test to measure students' accuracy in pronouncing 51 targeted phonemes. Classroom observations were done to document the application of the Reading Aloud technique during each cycle. The data were then analyzed quantitatively to evaluate the improvements the students have made in their pronunciation and to capture how the learning process has taken place. The finding continuous improvement from the preliminary study (46.97) to Cycle 1 (53.58) and Cycle 2 (66.36), with 63.63% of students achieving the success criteria. The result suggest that the use of Reading Aloud, supported by teacher modeling, corrective feedback, and repetitive practice can significantly enhance students’ pronunciation. This study contributes to the growing body of literature on pronunciation teaching and highlights the pedagogical value of Reading Aloud for EFL learners.